Science, business and universities : cooperation, knowledge transfer and entrepreneurship - Duda, Joanna (Economist); Bernat, Tomasz (Routledge studies in international business and the world economy, 2022)
"Cooperation between science and business (S2B cooperation) is a very important issue from the points of view of the domestic economy, companies, and universities. This is mainly because such cooperation is a catalyst for faster and reliable development - not only of enterprises, but also of the entire economy. Thanks to S2B cooperation, enterprises can gain and commercialize new and ground-breaking solutions. Universities in turn can give their research a more practical dimension to increase its economic applicability, which helps universities prepare future staff to work in modern enterprises. The aim of this publication is to indicate how cooperation between universities and business can be implemented in an international dimension. It shows the role of modern universities in supporting the development of enterprise and entire economies as well as the role of modern enterprises that use resources located in universities (including knowledge resources). This unique combination has a positive impact on the results and developmental opportunities for each of them. Any potential obtained in this manner is the basis for creating a competitive advantage on the market. This book is devoted to a specific area of cooperation between enterprises and universities and will be of interest to researchers, academics, practitioners, and students in the fields of entrepreneurship, knowledge management, international relations, and higher education"--